2019
DOI: 10.18773/austprescr.2019.002
|View full text |Cite
|
Sign up to set email alerts
|

Nitrofurantoin and fosfomycin for resistant urinary tract infections: old drugs for emerging problems

Abstract: Uncomplicated urinary tract infection is one of the most common indications for antibiotic use in the community. However, the Gram-negative organisms that can cause the infection are becoming more resistant to antibiotics. Many multidrug resistant organisms retain susceptibility to two old antibiotics, nitrofurantoin and fosfomycin. Advantages over newer drugs include their high urinary concentrations and minimal toxicity. Fosfomycin is a potential treatment option for patients with uncomplicated urinary tract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
84
1
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(99 citation statements)
references
References 58 publications
6
84
1
8
Order By: Relevance
“…[9][10][11][12]21,37]. Fosfomycin and nitrofurantoin both have unique chemical structures and mechanisms of action, therefore, these is no need to expect cross-resistance with other antibacterial drugs [9][10][11][12]21,38]. The utility of trimethoprim/sulfamethoxazole in the therapy of ESBL-positive and carbapenemasepositive Gram-negative isolates has been reported previously, both in UTIs and invasive infections [39]; nevertheless, this was not highlighted in our study.…”
Section: Resistotype Ciprofloxacinmentioning
confidence: 52%
“…[9][10][11][12]21,37]. Fosfomycin and nitrofurantoin both have unique chemical structures and mechanisms of action, therefore, these is no need to expect cross-resistance with other antibacterial drugs [9][10][11][12]21,38]. The utility of trimethoprim/sulfamethoxazole in the therapy of ESBL-positive and carbapenemasepositive Gram-negative isolates has been reported previously, both in UTIs and invasive infections [39]; nevertheless, this was not highlighted in our study.…”
Section: Resistotype Ciprofloxacinmentioning
confidence: 52%
“…(Giske, 2015). This could be mediated by point mutations in nsfA or nsfB, which metabolize nitrofurantoin into the reactive intermediates that interfere with ribosomal subunits, or by oxqAB in some Acinetobacter spp., but the LH6 sequenced strain does not possess these efflux genes (Sekyere, 2018;Gardiner et al, 2019). Previously, a high incidence of fluoroquinolone resistance was also found among the Listeria spp., while aminoglycoside resistance was found in E. coli and Salmonella spp.…”
Section: Discussionmentioning
confidence: 90%
“…Previously published clinical reports demonstrated that P. agglomerans can be responsible for a wide range of infections encompassing pneumonia, bladder and wound/skin infections, septicemia and meningitis [71]. While bacitracin is an antibiotic prescribed against skin infections, fosfomycin is an effective drug against bladder infections [72][73][74]. Vancomycin is used to treat meningitis, and rifampicin exerts antimicrobial activity against Mycobacterium species, as such being the antibiotic of choice prescribed against tuberculosis [75,76].…”
Section: Discussionmentioning
confidence: 99%